2005
DOI: 10.1093/hmg/ddi211
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial localization of the Parkinson's disease related protein DJ-1: implications for pathogenesis

Abstract: Both homozygous (L166P, M26I, deletion) and heterozygous mutations (D149A, A104T) in the DJ-1 gene have been identified in Parkinson's disease (PD) patients. The biochemical function and subcellular localization of DJ-1 protein have not been clarified. To date the localization of DJ-1 protein has largely been described in studies over-expressing tagged DJ-1 protein in vitro. It is not known whether the subcellular localization of over-expressed DJ-1 protein is identical to that of endogenously expressed DJ-1 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
297
1
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 391 publications
(312 citation statements)
references
References 50 publications
12
297
1
2
Order By: Relevance
“…The mitochondrial transcripts are also of interest because of the emerging evidence of a mitochondrial basis of recessive parkinsonism (2, 3). DJ-1 can be found on the surface of mitochondria (6) and within the mitochondrial matrix (28), supporting the idea that a small pool of DJ-1 may authentically associate with RNA in the mitochondria. However, this hypothesis requires additional confirmation.…”
Section: Discussionmentioning
confidence: 64%
“…The mitochondrial transcripts are also of interest because of the emerging evidence of a mitochondrial basis of recessive parkinsonism (2, 3). DJ-1 can be found on the surface of mitochondria (6) and within the mitochondrial matrix (28), supporting the idea that a small pool of DJ-1 may authentically associate with RNA in the mitochondria. However, this hypothesis requires additional confirmation.…”
Section: Discussionmentioning
confidence: 64%
“…DJͲ1 gene encodes a protein of 189 amino acids, belonging to the peptidase C56 family of proteins [263]. It is a cytoplasmic protein, but under stress conditions can also translocate into the mitochondria and nucleus [146,264]. WT DJͲ1 appears to exert an antioxidant function [265Ͳ268], while deletions and point mutations in the DJͲ1 gene cause a loss of its physiological function and therefore, lead to neurodegeneration in rare families [146, 269Ͳ271].…”
Section: Djǧ1mentioning
confidence: 99%
“…Furthermore, we have reported that DJ-1 activated TH and DDC through direct binding to TH and DDC in an oxidative status of DJ-1-dependent manner [24] and that human DJ-1 activates TH gene expression in cultured human dopaminergic cells [15]. DJ-1 is preferentially localized in the cytoplasm and nucleus [7] and a portion of DJ-1 is localized in the mitochondria [22,[25][26][27] and synapse [28].…”
Section: Introductionmentioning
confidence: 99%